1974
DOI: 10.1037/h0021530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two free-time reinforcement procedures on academic performance in a class of behavior problem children.

Abstract: Three behavior problem children, ages 11-14, who had been placed in a state mental health facility, were subjected to baseline and two sequential reinforcement conditions (reading reinforcement and chance reinforcement). The results indicate that free time can function as a reinforcer producing increases in the percentage of items answered correctly. Further, the results indicate that improvements can be affected in other academic subjects when only reading accuracy is reinforced. Finally, it was apparent that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Natural privileges in the classroom are good choices (Marholin, Mclnnis, & Heads, 1974;McLaughlin & Malaby, 1972). Often other school personnel will cooperate by letting students earn the right to be a library aide, office worker, or counselor assistant.…”
Section: Reinforcersmentioning
confidence: 99%
“…Natural privileges in the classroom are good choices (Marholin, Mclnnis, & Heads, 1974;McLaughlin & Malaby, 1972). Often other school personnel will cooperate by letting students earn the right to be a library aide, office worker, or counselor assistant.…”
Section: Reinforcersmentioning
confidence: 99%
“…Providing structured free-time contingent on task completion of tasks has been found to reinforce target behaviors by positive reinforcement, negative reinforcement, or a combination of both (Serna & Osborne, 1993;Zarconne, Fisher, & Piazza, 1996). Marholin II, McInnis and Heads (1974) found that contingent free-time increased the academic performance of three children with problem behaviors and Mahoney and McLaughlin (1989) were able to reduce verbal and behavioral interruptions in high school students. The use of structured free-time simultaneously rewards the child and can provide additional time to learn, whereas, a potential reinforcer such as tokens in a token economy or contingent praise might not.…”
mentioning
confidence: 99%
“…The effectiveness of teacher-administered rewards in changing children's classroom behaviour is well established in regard to both academic skill tasks (e.g. Hopkins, Schutte & Garton, 1971;Marholin, Mclnnes & Heads, 1974) and general compliance (e.g., Deitz & Repp, 1974;Hall, Lund & Jackson, 1968). The effectiveness of these rewards as reinforcers has long been recognized as dependent upon several components of the reward system, one of which is the contingency of the reward upon the emission of the behaviour that is to be increased or maintained (Bandura, 1969, p. 255).…”
mentioning
confidence: 99%